A clinical study on epidemiology and etiological factors of acute pancreatitis-hospital based study in South India - S., Rajesh; V., Raju P. (International Surgery Journal, 2021)
Background: Acute pancreatitis is an important cause of acute abdomen with high morbidity and mortality. This study aimed to evaluate the epidemiology and etiological factors of acute pancreatitis in a tertiary care hospital in South India. Methods: This retrospective study was carried among 70 patients. Data was collected and analysis done based on age, gender, etiology and severity of acute pancreatitis. Results: Males were found more commonly affected than females in the ratio (M:F) of 5:1. Mean age of the study group was 37.2 years and maximum incidence was seen in the age group of 31 to 40 years. Overall alcohol was the most common etiological factor followed by idiopathic cause and gall stone disease. Conclusions: Males were more commonly affected than females with acute pancreatitis. Alcohol and gall stones were the leading cause of acute pancreatitis in males and females respectively. Alcohol was the most common cause in this geographical location.